Small Molecules Organic Photovoltaic Devices Based on the Planar Heterojunction Porphyrin Derivates/Fullerene - Aguirre-Quintana, M; Aguirre-Quintana, M; Velez-Cifuentes, J (World Scientific Publishing Co. Pte Ltd, 2014)
In this paper, we studied of photoelectric properties of multilayer organic photovoltaic cells (OPV cells). The active organic layers consisted of a planar heterojunction between a layer of (meso-tetrakis(5-bromo-2-thienyl)porphyrin), (TBrTP) as electron donor (ED) and a layer fullerene molecules. For the manufacture of photovoltaic devices we use a the technique of high vacuum by thermal sublimation that allows multilayer devices realization easily by successive depositions, and it does not require solvents, achieving purer films with reproducible characteristics. The TBrTP allows achieving OPVCs exhibiting promising efficiencies when the ABL is the MoO3/CuI DABL. The CuI improves the current in the organic layer by one order of magnitude, which allows decreasing the series resistance of the OPVCs and therefore improving the OPVCs. © 2014 World Scientific Publishing Company.
Keywords: porphyrin derivative; organic solar cell; planar heterojunction